A new species of Chetoneura Colless from Borneo (Diptera: Keroplatidae) - Kazandzhieva, Svetlozara; Bechev, Dimitar (Zootaxa, 2022)
A new species of Keroplatidae—Chetoneura lagangеnsis sp. n. from Lagang cave in Sarawak, Borneo is described and illustrated based on a single male specimen. An identification key to the species of the genus Chetoneura Colless is provided. A distribution map of the five known species of Chetoneura is presented—Ch. cavernae Colless, Ch. shennonggongensis Amorim & Niu, Ch. oligoradiata (Papp), Ch. davidi Ševčík, Hippa & Burdiková and Ch. lagangensis Kazandzhieva & Bechev, sp. n.